Worker Training and Quality Competition - Christos Bilanakosa; John S. Heywood; John Sessions; Nikolaos Theodoropoulos (Global Labor Organization (GLO), 2017)
We uniquely examine the relationship between firm-sponsored training and product quality competition. Using an oligopolistic model of both price and quality competition, we show that an increase in the sensitivity of demand to product quality will strengthen firms' incentives to train their workforce. Cross section, panel and instrumental variable estimations confirm that British establishments provide more intensive training when their competitive position is more sensitive to product quality. A variety of robustness checks and changes in variable definitions leave this confirmation in place.
Keywords: L13; L15; M53; 330; Training; Product Quality; Demand Sensitivity; Competition